Micro-credentialing: a transformative tool for educator re-licensure and educator efficacy - Erickson, Paul William (Kansas State University, 2019)
Professional learning is and always has been a core expectation for educators. Professional learning comes in the conventional form of workshops, conferences, presentations and graduate degree programs. Professional learning also comes in the nonconventional form of social media, Personal Learning Networks (PLN’s), peer observations, and professional units of study known as micro-credentials. These pathways to professional learning are considered more personalized to the individual educator’s needs, interests, and strengths. This mixed-methods study is rooted in practitioner inquiry framework (Cochran-Smith & Lytle, 2009). The purpose of the study is to explore professional learning in the form of micro-credentials and its relationship with educator self-efficacy and educator collective efficacy. Participants will engage in a micro-credentialing study in which they complete multiple micro-credentials in an effort to meet their professional learning needs and earn re-licensure via Kansas State Department of Education/Teacher Licensure and Accreditation. Throughout the study, participants will complete surveys and engage in focus group interviews that assess their levels of self-efficacy and collective efficacy.
Keywords: Education; Leadership; Professional development; Personalized learning; Micro-credentials